An assessment of the risk of Bt-cowpea to non-target organisms in west Africa - Ba, Malick N.; Huesing, J.E.; Tamo, Manuele; Higgins, T.J.V.; Pittendrigh, B.R.; Murdock, L.L. (Springer, 2018)
Cowpea (Vigna unguiculata Walp.) is the most economically important legume crop in arid regions of sub-Saharan Africa. Cowpea is grown primarily by subsistence farmers who consume the leaves, pods and grain on farm or sell grain in local markets. Processed cowpea foods such as akara (a deep-fat fried fritter) are popular in the rapidly expanding urban areas. Demand far exceeds production due, in part, to a variety of insect pests including, in particular, the lepidopteran legume pod borer (LPB) Maruca vitrata. Genetically engineered Bt-cowpea, based on cry1Ab (Event 709) and cry2Ab transgenes, is being developed for use in sub-Saharan Africa to address losses from the LBP. Before environmental release of transgenic cowpeas, the Bt Cry proteins they express need to be assessed for potential effects on non-target organisms, particularly arthropods. Presented here is an assessment of the potential effects of those Cry proteins expressed in cowpea for control of LPB. Based on the history of safe use of Bt proteins, as well as the fauna associated with cultivated and wild cowpea in sub-Saharan Africa results indicate negligible effects on non-target organisms.